Leveraging AI Chatbots for Analyzing English Texts: Does It Diminish Critical Reading Skills? - Zumrotul Fauziah (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2026)
This study aimed to explore the influence of Artificial Intelligence (AI) chatbots on students’ critical reading skills in academic reading activities. The research focused on students’ abilities to identify main ideas, distinguish facts and opinions, recognize the author’s purpose and tone, make inferences, identify missing information, and draw logical conclusions from texts. A qualitative descriptive method was used, and data were collected through semi-structured interviews with 10 undergraduate EFL students in the Islamic Education study program at Nahdlatul Ulama Sunan Giri University, comprising 2nd-, 4th-, and 8th-semester students. The findings showed that students frequently used AI chatbots, such as ChatGPT and Gemini, to summarize texts, explain difficult concepts, and improve reading comprehension. Most participants considered AI helpful in understanding academic materials more efficiently. On the other hand, many participants perceived that frequent AI usage increased their dependence on technology and reduced their independent critical reading practices, especially in making inferences and drawing conclusions. Meanwhile, the analysis of students’ reading tasks indicates that students generally performed better at distinguishing facts from opinions than at identifying important information, making inferences, and drawing logical conclusions. It can be concluded that frequent AI use has weakened certain higher-order critical reading skills, particularly those involving independent analysis, inference, and drawing conclusions. Therefore, the use of AI chatbots should be responsible and balanced in EFL learning contexts. Critical reading skills are necessary for analyzing English texts.